Clinical application of gancyclovir in the complex treatment of the different forms of true acantholytic pemphigus - M. K. Baltabaev; A. M. Baltabaev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Short summary and results of the own clinical observations on efficacy of developed complex method on the treatment of true acantholytic pemphigus composed of traditional immunosuppressive therapy and antiviral remedy - gancyclovir are presented. The etiology of herpesvirus infection had been discussed in the pathogenesis of the disease.